PERENCANAAN RESCUE BOAT KAPASITAS ANGKUT 10 ORANG UNTUK EVAKUASI MASYARAKAT TERDAMPAK BANJIR DI KELURAHAN KEBON PALA - Sahrul Ramadani (2021)
From the data obtained, the size is determined by adjusting to the conditions of the surrounding environment. The main sizes that meet the main walking criteria are LoA: 7 m, B: 2 m, H: 0.2 m. For those that reach small alleys, a smaller rescue boat is used. This was made to immediately evacuate many flood victims who were in the alleys with a smaller variation of the rescue boat. From the data obtained, this small rescue boat has a main size of LoA: 3.17 m, B: 1 m, T: 0.4 m to operate on smaller aisles. In the rescue ship resistance using the selender body method, a total resistance of 5 kN was obtained, assuming a propulsion efficiency of 60% required a power of 28.783 HP to move the ship to a maximum speed of 2 knots and 5 knots. The reason for choosing to use a slender boy over a holtrop is because the ship's geometry does not meet the requirements to be calculated using Holtrop. LWL is too low to be calculated using a holtrop, and with an LWL of that size B is considered too large. Although Holtrop is usually used for calculating ships with monohull hulls, such as tankers or fishing vessels. On the stability of large and small rescue ships, the results obtained from the stability analysis with a Maximum GZ of 40 degrees have passed the requirements or Criteria rules from IMO A.749 (18) Ch.3.